(untitled) (International Journal of Food and Nutritional Sciences, 2022)
labeling is an assignment of integers, either to the vertices or edges, or both , subject to certain conditions. Prime labeling is , in an edge adjacent vertices are relatively prime to each other. In this paper we discussed prime labeling of Pn (+) Nm graph, star graphs, and Alternate quadrilateral snake by unique way.